Handbook of environmental economics. - Dasgupta, Partha; Pattanayak, Subhrendu; Smith, V. Kerry (Vincent Kerry), 1945- (Handbooks in economics., 2018)
Handbook in Environmental Economics, Volume 4, the latest in this ongoing series, highlights new advances in the field, with this new volume presenting timely chapters on Modeling Ecosystems and Economic Systems, Framing Sustainability Policy Questions: Who Leads - Ecology or Economics?, Valuing Natural Capital Within an Integrated Economic Ecological, Developing Economies, Urbanization, Climate Change and Health, Viewing Environmental Policy Instruments for Domestic and International Perspective, Quasi experimental Estimation of Environmental Policies, Environment Macro, The Rules for Formal and Informal Institutions in Managing Environmental Resources, and How Should Uncertainty Be Integrated into the Methods for Policy Evaluation?